Detection of inhibitors of Candida albicans Cdr transporters using a diS-C3(3) fluorescence - Szczepaniak, Joanna; Łukaszewicz, Marcin; Krasowska, Anna (Frontiers in Microbiology, 2015)
Candida albicans is a major cause of opportunistic and life-threatening, systemic fungal infections. Hence new antifungal agents, as well as new methods to treat fungal infections, are still needed. The application of inhibitors of drug-efflux pumps may increase the susceptibility of C. albicans to drugs. We developed a new fluorescence method that allows the in vivo activity evaluation of compounds inhibiting of C. albicans transporters. We show that the potentiometric dye 3,3′-dipropylthiacarbocyanine iodide diS-C3(3) is pumped out by both Cdr1 and Cdr2 transporters. The fluorescence labeling with diS-C3(3) enables a real-time observation of the activity of C. albicans Cdr1 and Cdr2 transporters. We demonstrate that enniatin A and beauvericin show different specificities toward these transporters. Enniatin A inhibits diS-C3(3) efflux by Cdr1 while beauvericin inhibits both Cdr1p and Cdr2p.